Ionizing radiation for preparation and functionalization of membranes and their biomedical and environmental applications - Casimiro, Maria Helena (2020)
UID/Multi/04349/2019. IST-ID/077/2018. IST-ID/076/2018. POCI-01-0145-FEDER -007265.